PENGARUH LINGKUNGAN MULTIKULTURAL TERHADAP IDENTITAS SOSIAL REMAJA DI PONDOK PESANTREN ULUMUL QUR’AN AL-QINDLIYYAH - Zaidatun Ni’mah Julifiyana; Auliya Sholikhatun; Nurul Mubin (JOURNAL SAINS STUDENT RESEARCH, 2024)
It is essential to understand how the multicultural environment in Islamic boarding schools contributes to the formation of adolescents' social identity and how these schools play a role in fostering harmony amidst diversity. This study employs a qualitative approach to explore in-depth the social phenomena, particularly the interaction between the multicultural environment and the process of forming social identity among adolescents at Ulumul Qur'an Al-Qindiliyyah Islamic boarding school. The success in shaping an inclusive social identity demonstrates that multicultural boarding schools can serve as educational models that not only strengthen religious values but also integrate cultural values from the broader society.